1994
DOI: 10.1007/bf02592441
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise and hemostasis

Abstract: A number of hemostatic changes involving platelets, coagulation and fibrinolysis have been reported after acute physical exercise. Results have sometimes been controversial, due to differences in subjects investigated, type of exercise and methods used for hemostatic evaluation. On the whole, physical exercise has been shown to induce: (1) increases in platelet number and activity, (2) activation of coagulation leading to a slight but significant thrombin generation and (3) activation of fibrinolysis. These ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
2
19
0
6
Order By: Relevance
“…119 For example, acute exercise increases some clotting factors (particularly factor VIII and von Willebrand factor), and this has been associated with a reduction in clotting time, but it is unclear whether this leads to significant thrombin generation and/or fibrin formation. 120,121 Many of these changes disappear quickly during recovery from exercise, although other factors may take as long as 48 hours to return to baseline levels. 122 There is considerable interindividual variability in the response to acute exercise, and these responses are dependent on exercise intensity, suppressed by ␤-blockade, enhanced by catecholamine responses, and more pronounced among patients with coronary artery disease.…”
Section: Thrombosismentioning
confidence: 99%
See 3 more Smart Citations
“…119 For example, acute exercise increases some clotting factors (particularly factor VIII and von Willebrand factor), and this has been associated with a reduction in clotting time, but it is unclear whether this leads to significant thrombin generation and/or fibrin formation. 120,121 Many of these changes disappear quickly during recovery from exercise, although other factors may take as long as 48 hours to return to baseline levels. 122 There is considerable interindividual variability in the response to acute exercise, and these responses are dependent on exercise intensity, suppressed by ␤-blockade, enhanced by catecholamine responses, and more pronounced among patients with coronary artery disease.…”
Section: Thrombosismentioning
confidence: 99%
“…122 There is considerable interindividual variability in the response to acute exercise, and these responses are dependent on exercise intensity, suppressed by ␤-blockade, enhanced by catecholamine responses, and more pronounced among patients with coronary artery disease. 118,119,121 In contrast to acute exercise, both higher physical activity patterns and structured exercise programs have an inhibitory effect on thrombogenic factors and enhance blood fibrinolytic potential. 119,[123][124][125][126][127] These changes have been demonstrated in both healthy subjects and patients with cardiovascular disease and occur across a broad range of factors involved in the coagulation cascade.…”
Section: Thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…During coagulation, fibrinogen is converted to fibrin by means of thrombin and ionized calcium. The exercise contributes partly to this coagulation activation leading to a small but significant thrombin generation and activation of fibrinolysis (Mavrovouniotis, 2012;Prisco et al, 1994). Kumar, Kar and Fay (2011) and Wosornu et al (1992) concluded that aerobic exercise following a coronary bypass that causes drop in fibrinogen concentration increases the success rate of the graft and reduces the chances of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%